James B. Pick, Edgar W. Butler y Elizabeth L. Lanza [i.e. Lanzer]. Atlas of Mexico. San Francisco : Westview Press, 1989. 367 p. - Muñoz Contreras, María Elena (El Colegio de México A.C., 1989)
JAMES B. PICK, EDGAR W. BUTLER y ELIZABETH L. LANZA, Atlas of Mexico. Westview Press, San Francisco, 1989.